Pengaruh Pendidikan Kesehatan Gigi (DHE) Terhadap Indeks Plak Penderita Schizophrenia Di Rumah Sakit Jiwa Daerah Surakarta - Indriastuti, Latty; , drg. Edi Karyadi, M.M; , drg. SE Yuletnawati, MDSc (2014)
Patient with schizophrenia have abnormality in psychological condition that affect on their oral hygiene. Therefore, a suitable media on supporting Dental Health Education was needed in order to optimize the education itself. The effective media for helping patient with mental disorder is the combination of audio, visual and audiovisual, because the content of dental education that have been delivered can improve object's behavior in maitaining their oral hygiene. The aim of this research was to explore the effect of Dental Health Education towards plaque index of patients of schizophrenia at Mental Illness Hospital in Surakarta. This research used Quasi Experimental research with Pretest and Posttest Only Design. The research's subjects were 40 cooperative psycosis patients specified in schizophrenia. Each subjects has been treated for plaque inspection as initial treatment using O'Leary Plaque Control Record. Dental Health Education then had given by using alarm as audio, poster as visual and video tutorial of how to brushing teeth for audiovisual for a week. After that, post treatment of plaque index arranged. The result of research showed significant value p=0,000 (p<0,05) for plaque score pre Dental Health Education and post Dental Health Education. According to this result, Dental Health Education gave a good effect in decreasing plaque index on patient with schizophrenia at Mental Illness Hospital in Surakarta.